INTANGIBLES RESOURCES AND CORPORATE PERFORMANCE: THE ROLE OF CORPORATE ENTREPRENEURSHIP AS MEDIATOR AND ENTREPRENEURIAL ACTION AS MODERATOR - Wahjudono, Denny Bernardus Kurnia (Jurnal Aplikasi Manajemen, 2017)
This study examined the mediating role of corporate entrepreneurship in the effects of corporate reputation, strategic leadership, and corporate culture on corporate performance, in turn, the moderating role of entrepreneurial action in the relationship between corporate entrepreneurship and corporate performance. This study was organization- level of 24 business units. From each business unit, this study selected six to nine respondents consisting of the general manager, manager, supervisor, and senior staff; 156 respondents totally. Structural equation modeling with Partial Least Squares (SEM-PLS) was used to test the measurement model of each construct. In addition, SEM-PLS also used to verify the mediating role of corporate entrepreneurship as well as the moderating role of entrepreneurial action. The results showed that corporate reputation, strategic leadership, and corporate culture were positively associated with corporate performance through corporate entrepreneurship as a mediator. Moreover, the relationship between corporate entrepreneurship and corporate performance was strengthened by entrepreneurial action. Entreprises should develop, maintain, and improve their intangibles resources to provide the good entrepreneurship value for them. The good entrepreneurship value may improve the corporate performance which strengthened by entrepreneurial action.